2022
DOI: 10.3390/axioms11110620
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Deep Learning Algorithm for Forecasting SARS-CoV-2 Daily Infections and Death Cases

Abstract: The prediction of new cases of infection is crucial for authorities to get ready for early handling of the virus spread. Methodology Analysis and forecasting of epidemic patterns in new SARS-CoV-2 positive patients are presented in this research using a hybrid deep learning algorithm. The hybrid deep learning method is employed for improving the parameters of long short-term memory (LSTM). To evaluate the effectiveness of the proposed methodology, a dataset was collected based on the recorded cases in the Russ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…During the COVID-19 pandemic, a substantial effort has been made to develop ML models to either predict case numbers from epidemiological data [ 3 , 4 , 5 , 6 , 7 ] or to classify SARS-CoV-2 sequences using genomic data [ 28 , 29 , 30 , 31 ], but in most situations, there was no attempt to explain the output of these models. With recent progress in model explainability, ML models are less and less considered as black boxes, and explaining them is especially important in epidemiology and biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, a substantial effort has been made to develop ML models to either predict case numbers from epidemiological data [ 3 , 4 , 5 , 6 , 7 ] or to classify SARS-CoV-2 sequences using genomic data [ 28 , 29 , 30 , 31 ], but in most situations, there was no attempt to explain the output of these models. With recent progress in model explainability, ML models are less and less considered as black boxes, and explaining them is especially important in epidemiology and biology.…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of the seminal work of the late Sir Robert May [ 1 ], most of modern epidemiology aims at predicting the severity of viral outbreaks based on the number of individuals who are susceptible, infected, and recovered (or dead) in a population—that is, based on epidemiological data, as has been the case, for instance, during the COVID-19 pandemic, caused by the SARS-CoV-2 virus [ 2 ]. Complementary approaches have nonetheless resorted to machine learning (ML) to improve predictions, but these applications mainly focused on the same kind of epidemiological data [ 3 , 4 , 5 , 6 , 7 ] or on image processing to diagnose the disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the COVID-19 pandemic (global pandemic) becomes a global pandemic (pandemic), it is necessary to conduct an epidemiological investigation in real time to provide the public with a clear direction to fight the infection. According to [ 3 ], the authors utilized a combined CNN-LTSM model using a time-series dataset to predict the confirmed cases of COVID-19 [ 33 ]. The CNN-LTSM encoder-decoder technique helps significantly boost prediction performance [ 34 ].…”
Section: Literature Surveymentioning
confidence: 99%
“…In "Hybrid Deep Learning Algorithm for Forecasting SARS-CoV-2 Daily Infections and Death Cases" by Fehaid Alqahtani, Mostafa Abotaleb, Ammar Kadi, Tatiana Makarovskikh, Irina Potoroko, Khder Alakkari, and Amr Badr [8], the authors used a hybrid deep learning algorithm to predict new cases of infection which is crucial for authorities to get ready for early handling of the virus spread. The hybrid deep learning method was used to improve the parameters of long short-term memory (LSTM).…”
mentioning
confidence: 99%